Factors related to Icelandic student teachers' prospective commitment to the teaching profession - Elstad, Eyvind; Bjørnsdottir, Amalia; Christophersen, Knut-Andreas; Jóhannsdóttir, thuríður Jóna; Turmo, Are (University of Aberdeen, 2021)
Research indicates that prospective commitment to a vocation is important to sustaining good professional practices. The purpose of the study was to explore, among Icelandic student teachers, how student teacher experiences in field-based practice and those in university-based courses are related to the student teachers’ prospective commitment to the teaching profession as well as their possible turnover intentions. This study investigated the experiences of student teachers in a five-year programme for compulsory schoolteachers at the University of Iceland. The data is based on results from a survey of 244 student teachers in all cohorts in the programme. In particular, we investigated connections between the attitudes of student teachers towards the teaching profession and their experiences during the university-based part of their teacher education and during the school-based teaching practice aspect. The data analysis indicates that the university-based part of teacher education positively influences student teachers’ commitment to the teaching profession and negatively influences their turnover intentions, while the school-based component of their teacher education is positively related to their commitment to the teaching profession but is not related to their turnover intentions. The implications of the findings are discussed.